NILAI-NILAI KRISTIANI DALAM KEPEMIMPINAN PELAYAN - Maria Merry Marianti (Center for Economic Studies Universitas Katolik Parahyangan, 2011)
Servant-leadership is one of the frontier leadership theories. Love is the basic characteristic of Servant Leadership, ending with Service, which is the main motivation of a Servant Leader. Values that embedded are Servant Leadership is Christian Values.